New oxford textbook of psychiatry - Geddes, J. R. John R.; Andreasen, N. C. Nancy C.; Goodwin, G. M. Guy M. (Oxford university press, 2020)
Over its two editions, The New Oxford Textbook of Psychiatry has come to be regarded as one of the most popular and trusted standard psychiatry texts among psychiatrists and trainees. Bringing together 146 chapters from the leading figures in the discipline, it presents a comprehensive account of clinical psychiatry, with reference to its scientific basis and to the patient's perspective throughout. The New Oxford Textbook of Psychiatry, Third Edition has been extensively re-structured and streamlined to keep pace with the significant developments that have taken place in the fields of clinical psychiatry and neuroscience since publication of the second edition in 2009. The new edition has been updated throughout to include the most recent versions of the two main classification systems---the DSM-5 and the ICD-11---used throughout the world for the diagnosis of mental disorders. In the years since publication of the first edition, many new and exciting discoveries have occurred in the biological sciences, which are having a major impact on how we study and practise psychiatry. In addition, psychiatry has fostered closer ties with philosophy, and these are leading to healthy discussions about how we should diagnose and treat mental illness. This new edition recognises these and other developments. Throughout, accounts of clinical practice are linked to the underlying science, and to the evidence for the efficacy of treatments. Physical and psychological treatments, including psychodynamic approaches, are covered in depth. The history of psychiatry, ethics, public health aspects, and public attitudes to psychiatry and to patients are all given due attention.